Natural or Artificial: Is the Route of L2 Development Teachable?. Issue 1 (March 2015) - Zhang, Xian; Lantolf, James P.; Hulstijn, Jan H.; Ellis, Rod; Eskildsen, Søren W.
<x xml:space="preserve">Abstract</x> The current study was designed to assess the central claim of the Teachability Hypothesis (TH), a corollary of general Processability Theory (PT), which predicts instruction cannot alter posited universal, hierarchically organized psycholinguistic constraints behind PT's developmental sequences. We employed an interventional design, which adhered to instructional procedures of Systemic Theoretical Instruction, and we taught four university learners at Stage 2 (subject‐verb‐object) Chinese topicalization for Stage 4 (object‐first, e.g., Pizza tā yě chī le, Pizza 他 也 吃了, 'Pizza he also ate'). We believe the findings show that, under the instructional conditions utilized in the study, the predictions of TH do not hold. We conclude it is possible to artificially construct a developmental route different from the one predicted by natural developmental sequences, in agreement with the claims of Vygotsky's developmental education.